Besin etiketlerinin sağlık algısı üzerine etkisi - Vergi, Yeliz (My University, 2018)
Amaç: Farklı fakültelerde eğitim gören öğrencilerin besin etiketlerini okumalarıve sağlık algıları arasındaki ilişkinin değerlendirilmesidir.Gereç ve Yöntem: Kesitsel tipte tanımlayıcı olarak yapılan araştırmada,tabakalı örneklem yoluyla yüzyüze görüşme yöntemi ile farklı fakültelerde eğitimgören öğrencilere (n:1578), sosyodemografik özellikler ile besin etiketleri okumaalışkanlıklarını kapsayan sorular içeren anket ve sağlık algısını ölçmeye yönelikgeliştirilen ölçek uygulanmıştır. Araştırmacı tarafından geliştirilen ölçeğin geçerlilikve güvenilirliği yapılmış ve alpha: 0,874 olarak Yüksek bulunmuştur. Elde edilenveriler SPSS istatistik paket programında değerlendirilmiştir.Bulgular: Katılımcıların %62’si kadındır. Sağlıkla ilgili fakültelerde eğitimalanlar %62,2’dir. Besin etiketleri genel okuma alışkanlığı %90’dır. Sağlık algısıölçeği genel puan ortalaması (20,518±6,510) olup fakültelere göre sağlığınkorunması, bilgi düzeyi, davranışa geçirme ve sağlık algısı genel ortalamalarıarasındaki fark ve besin etiketi okuma alışkanlığı olanların olmayanlara göre;sağlığın korunması, davranışa geçirme ve sağlık algısı genel puan ortalamalarıarasındaki fark istatistiksel açıdan anlamlıdır (p<0,05).Sonuç: Toplumun sağlık algısının gelişmesi, sağlık okuryazarlık düzeyininiyileştirilmesi için üniversite öğrencilerinde besin etiketi okuma alışkanlığınınönemli olduğu saptanmıştır.

Objective: The purpose of this research is to observe and determine the correlationbetween this habit and its effects on overall different among university students.Materials and Methods: This research consists of students from different faculties.In this cross-sectional research, a questionnaire is presented to 1578 students byusing a stratified sampling method. As research`s data collecting method; the scaledeveloped by researcher to assess the perception of health in individuals and thequestionnaire mainly focused on sociodemographic features and the habit of readingfood labels were utilized. Reliability and security of the scale were analyzedstatically and alpha were highly in 0,874.Findings: According to findings, 62% of the participants were women, 62,2% of thepopulation were students of Faculty of Health Sciences. Besides, 90% of participantshas general habit of reading food labels. The average scale score were; ``perceptionof health``(20,518±6,510) and the differences between the means from faculties inpreservation of health, knowledge level, behavioral efficiency and understanding ofhealth are statistically significant (p<0.05). Participants who don't have habit ofreading food labels, scored lower in ``preservation of health``, ``behavioralefficiency`` and ``understanding of health`` are statistically significant (p<0.05).Results: In this research, it is found that the habit of reading food labels plays animportant role in the development and maintenance for perception of health. It isrecommended that providing health literacy education is necessity for students.
Keywords: Besin etiketi; Food label; Health literacy; Health perception; Healthy nutrition; Öğrenciler (Yüksek okul); Sağlık algısı; Sağlık okuryazarlığı; Sağlıklı beslenme; sağlıklıbeslenme food label; Students (College); Turkey; Turkey (College); Türkiye